2002
DOI: 10.4049/jimmunol.169.11.6452
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Membrane IL-5 Receptor α on Human Eosinophils: I. Loss of Membrane IL-5 Receptor α on Airway Eosinophils and Increased Soluble IL-5 Receptor α in the Airway After Allergen Challenge

Abstract: IL-5 is a key cytokine for eosinophil maturation, recruitment, activation, and possibly the development of inflammation in asthma. High concentrations of IL-5 are present in the airway after Ag challenge, but the responsiveness of airway eosinophils to IL-5 is not well characterized. The objectives of this study were to establish, following airway Ag challenge: 1) the expression of membrane (m)IL-5Rα on bronchoalveolar lavage (BAL) eosinophils; 2) the responsiveness of these cells to exogenous IL-5; and 3) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
162
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(188 citation statements)
references
References 37 publications
21
162
2
Order By: Relevance
“…Studies by Bates et al (38) using eosinophils obtained from bronchoalveolar lavage fluid documented a decreased responsiveness of cells to IL-5 stimulation that was paralleled by a decreased expression of the ␣-chain of the IL-5 receptor. These findings were independently confirmed by Liu et al (36,37) who reported distinct regulation of the receptors for IL-3, GM-CSF, and IL-5. In vitro studies showed that 24 h of stimulation of eosinophils with IL-5 resulted in the down-regulation of expression of the ␣-chains of the receptors for IL-5 and GM-CSF and in up-regulation of the ␣-chain of the IL-3 receptor (30).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Studies by Bates et al (38) using eosinophils obtained from bronchoalveolar lavage fluid documented a decreased responsiveness of cells to IL-5 stimulation that was paralleled by a decreased expression of the ␣-chain of the IL-5 receptor. These findings were independently confirmed by Liu et al (36,37) who reported distinct regulation of the receptors for IL-3, GM-CSF, and IL-5. In vitro studies showed that 24 h of stimulation of eosinophils with IL-5 resulted in the down-regulation of expression of the ␣-chains of the receptors for IL-5 and GM-CSF and in up-regulation of the ␣-chain of the IL-3 receptor (30).…”
Section: Discussionsupporting
confidence: 62%
“…In vitro studies showed that 24 h of stimulation of eosinophils with IL-5 resulted in the down-regulation of expression of the ␣-chains of the receptors for IL-5 and GM-CSF and in up-regulation of the ␣-chain of the IL-3 receptor (30). Although these findings suggested a role for IL-3-mediated activated eosinophils in lung eosinophils, further studies showed down-regulation of GMR␤ upon IL-5 stimulation in both in vitro and in vivo models (36,39). Taken together, down-regulation of the GMR␤ receptor that extended beyond 18 h after in vitro stimulation and decreased GMR␤ expression observed in bronchoalveolar lavage eosinophils after segmental allergen challenge suggested the relative independence of late signaling events from cytokine stimulation with GM-CSF, as well as IL-5 and IL-3.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, a recent study has proved that a significant number of eosinophils exist in the bronchial mucosa in asthmatic patients treated with anti-IL-5 antibody (Flood-Page et al 2002). In support of these findings, Liu et al (2002) have also reported the loss of IL-5 receptor a on airway eosinophils after allergen challenge, which may explain the ineffectiveness of anti-IL-5 antibody. If eosinophil deletion could be achieved by treatment with low molecular weight chemicals, which might penetrate more easily into peripheral inflammatory tissues, the significance of the role of eosinophils would be established, and the controversy would be resolved.…”
Section: Strategies Used To Develop Anti-allergic Drugs Active At Nr4supporting
confidence: 53%
“…The Leckie paper also did not consider IL-5 receptor expression and function of the eosinophils obtained in airway fluid in comparison with blood or tissue eosinophils. Liu et al demonstrated a marked reduction in the expression of messenger RNA of the surface IL-5 receptor (mIL-5Ra) and its intracellular component (mIL-5Rb) from BAL eosinophils compared with blood eosinophils (17). Further, in contrast to circulating eosinophils, BAL eosinophils do not release eosinophil-derived neurotoxin (EDN) when treated with IL-5 as do their blood counterparts, suggesting that the function of BAL eosinophils are IL-5-independent (18).…”
Section: The Resurrection Of the Eosinophil As An Important Effector mentioning
confidence: 99%